Inhibition Of TNF-α Release by D : B- Friedo - Olean -5- En- 3α -Ol in Human Monocytes - Tantely, Andriamampianina Tianarilalaina; Patricia, Randrianavony; Herilala Lea, Rasoanaivo; Fanantenanirainy, Pr Randimbivololona (European Scientific Journal, ESJ, 2016)
This study was focused on the release of TNF- α by cultured monocytes of human blood in the absence and presence of D : B Friedo - olean - 5 -en- 3α -ol (DBFO). The human monocytes were isolated from the peripheral blood mononuclear cells (PBMC). The release of TNF-α by monocytes was induced by the addition of lipopolysaccharide (LPS) to the culture medium. ELISA Sandwich’s method was used to the dosing of TNF- α concentration. The release of TNF-α is inhibited by DBFO. In the absence of DBFO, TNF- α concentration is 3.86 ng/ml versus 3.77 ; 3.2 ; 2.79 and 0.89 ng/ml in the presence of DBFO at concentrations 1 , 3, 10 and 30 μg/ml respectively ( p <0.05) .